Towards a better integration of social sciences in arbovirus research and decision-making: an experience from scientific collaboration between Cuban and Quebec institutions. (December 2020) - Carabali, Mabel; Pérez, Dennis; Degroote, Stephanie; Reyes, Alicia; Kaufman, Jay S.; Ridde, Valery
In 2017, the Institute of Tropical Medicine Pedro Kourí, University of Montreal Public Health Research Institute, and McGill University joined efforts to provide scenarios for scientific exchange and knowledge dissemination about the social science contribution on arboviral research. This commentary describes the scientific collaboration between Cuban and Canadian (Quebec) institutions, illustrating the need and opportunities to facilitate research and effective decision-making processes for arboviral prevention and control, going beyond traditional biomedical aspects. We organized a set of scientific activities within three international events conducted in Cuba between 2017 and 2018. Given the collaborating institutions' expertise and the knowledge gaps in arboviral research, we selected three main thematic areas: social determinants and equity, community-based interventions and use of evidence for decision-making. The partnership shows that interdisciplinary collaboration and the use and integration of quantitative and qualitative methods from the social sciences is essential to face the current challenges in arbovirus research.